Quantitative single-cell analysis of Leishmania major amastigote differentiation demonstrates variably extended expression of the lipophosphoglycan (LPG) virulence factor in different host cell types. - Michael A Mandell; Wandy L Beatty; Stephen M Beverley (Public Library of Science (PLoS), 2022)
Immediately following their deposition into the mammalian host by an infected sand fly vector, Leishmania parasites encounter and are engulfed by a variety of cell types. From there, parasites may transit to other cell types, primarily macrophages or dendritic cells, where they replicate and induce pathology. During this time, Leishmania cells undergo a dramatic transformation from the motile non-replicating metacyclic stage to the non-motile replicative amastigote stage, a differentiative process that can be termed amastigogenesis. To follow this at the single cell level, we identified a suite of experimental 'landmarks' delineating different stages of amastigogenesis qualitatively or quantitatively, including new uses of amastigote-specific markers that showed interesting cellular localizations at the anterior or posterior ends. We compared amastigogenesis in synchronous infections of peritoneal and bone-marrow derived macrophages (PEM, BMM) or dendritic cells (BMDC). Overall, the marker suite expression showed an orderly transition post-infection with similar kinetics between host cell types, with the emergence of several amastigote traits within 12 hours, followed by parasite replication after 24 hours, with parasites in BMM or BMDC initiating DNA replication more slowly. Lipophosphoglycan (LPG) is a Leishmania virulence factor that facilitates metacyclic establishment in host cells but declines in amastigotes. Whereas LPG expression was lost by parasites within PEM by 48 hours, >40% of the parasites infecting BMM or BMDC retained metacyclic-level LPG expression at 72 hr. Thus L. major may prolong LPG expression in different intracellular environments, thereby extending its efficacy in promoting infectivity in situ and during cell-to-cell transfer of parasites expressing this key virulence factor.